Produtividade da cana-de-açúcar fertirrigada com N e K via gotejamento subsuperficial - Dalri, Alexandre B.; Cruz, Raimundo Leite [UNESP] (Soc Brasil Engenharia Agricola, 2008)
The objective of this work consisted in the study of the fertigation and subsurface drip irrigation in the sugarcane productivity, in the second and the third seasons and technological effects in the growth. The experiment was developed in the experimental area of the Agronomical Sciences Faculty, FCA/UNESP - Botucatu, Brazil. The drip pipe was installed at 30 cm of depth and under the plantation line of sugar cane RB 72454 variety. The fertigation treatment with the biggest dose presented the better yield, with 190.01 t ha(-1) and 168.80 t ha(-1) to the second and the third harvest, respectively. The fertigation did not modify the technological qualities of the sugarcane in the two studied seasons, and the irrigation provided 43.5% and 67.2% of increments in the production of stem, to the second and third cut, respectively.
Productivity of sugarcane fertigation with nk by subsurface drip
Keywords: fertigation; Saccharum spp.; drip irrigation